Collective Bargaining in Higher Education and the Professions, Bibliography No. 14 - Douglas, Joel M., Comp.; City Univ. of New York, NY. Bernard Baruch Coll. National Center for the Study of Collective Bargaining in Higher Education and the Professions ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
A bibliography of 1,187 publications and court cases concerning employment of college faculty, as well as health professionals, is presented. Most of the publications cover the years 1982-1985. The faculty section covers the following topics: academic freedom, accountability, administration, affirmative action, arbitration and mediation, collective bargaining, community colleges, contracts, department heads, discipline and dismissal, discrimination, due process, elections, evaluation, excellence, faculty attitudes, faculty organizations, fiscal issues, fringe benefits, governance, grievance procedures, legal issues, legislation, academic librarians, National Labor Relations Board (NLRB), part-time faculty, personnel administration, quality of worklife, retirement, retrenchment, students, strikes, salaries, tenure, women faculty, workload, and the Yeshiva University case. The bibliography for related professions covers the health care institution and administration, dental/medical school faculty, nurses, and physicians. Also covered are state and federal court cases, U.S. Supreme Court decisions, and NLRB decisions. Directories, bibliographies, resources, periodicals, and information sources are listed. Indices of subject, author, and court cases and administrative orders are included. (SW)
Availability: National Center for the Study of Collective Bargaining in Higher Education and the Professions, Baruch College, City University of New York, 17 Lexington Avenue, Box 322, New York, NY 10010 ($20.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Collective Bargaining; College Faculty; Court Litigation; Employment Practices; Faculty College Relationship; Health Personnel; Higher Education; Nurses; Personnel Policy; Physicians; Teacher Employment; Unions; Excellence In Education; Reference Materials, Bibliographies